2016
DOI: 10.3164/jcbn.15-137
|View full text |Cite
|
Sign up to set email alerts
|

The effect of astaxanthin on vascular endothelial growth factor (VEGF) levels and peroxidation reactions in the aqueous humor

Abstract: We explored the effect of astaxanthin on vascular endothelial growth factor in the aqueous humor, by measuring vascular endothelial growth factor levels and oxidation-related parameters, including O2•− scavenging activity, H2O2 level, and total hydroperoxide level in the aqueous humor, obtained from 35 patients before and after astaxanthin administration. We evaluated the relationship between vascular endothelial growth factor and the oxidation-related parameters as well as the patient’s diabetic status, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Systemic AST supplementation could function in the eye and potentially protect the retina from various diseases by reducing oxidative stress. Oral AST supplementation has been used in previous randomized controlled trials and was found to suppress the aqueous vascular endothelial growth factor levels and peroxide production in humans [64,65]. An earlier trial using AST in combination with lutein and other antioxidants also reported improved central visual function in patients with age-related macular degeneration [66].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic AST supplementation could function in the eye and potentially protect the retina from various diseases by reducing oxidative stress. Oral AST supplementation has been used in previous randomized controlled trials and was found to suppress the aqueous vascular endothelial growth factor levels and peroxide production in humans [64,65]. An earlier trial using AST in combination with lutein and other antioxidants also reported improved central visual function in patients with age-related macular degeneration [66].…”
Section: Discussionmentioning
confidence: 99%
“…•scavenging activity and H 2 O 2 and TH level) and VEGF level. (12)(13)(14)(15)(16)(17) The relationships between these parameters and VEGF level were analyzed according to sex before and after AX intake. Correlations between parameters were analyzed using Pearson's correlation coefficient, and quantitative changes before and after AX intake were analyzed using Wilcoxon's signed rank sum test.…”
Section: Methodsmentioning
confidence: 99%
“…•-, H 2 O 2 , and TH). (12) We further performed multivariate analysis on the contributions of factors such as sex, age, and diabetic status of patients to the levels of VEGF in the aqueous humor and to the change in VEGF levels following AX intake. Our findings were: (i) that the primary factor affecting VEGF levels in the aqueous humor before and after the AX intake is TH, and that the levels of VEGF in the aqueous humor and TH correlated with each other; and (ii) that a secondary factor affecting VEGF levels in the aqueous humor before AX intake is superoxide (O 2…”
mentioning
confidence: 99%
“…•scavenging activity and suppression of peroxide formation, (11) while VEGF levels were related to total hydroperoxides levels in the aqueous humor and AX intake affected O 2…”
mentioning
confidence: 98%
“…We previously reported several findings, (6)(7)(8)(9)(10)(11)(12) including a beneficial anti-inflammatory effect of AX after cataract surgery. (6) AX intake also increased superoxide (O 2…”
mentioning
confidence: 99%